Design of a dual pH and temperature responsive hydrogel based on esterified cellulose nanocrystals for potential drug release. (15th February 2022) - Emam, Hossam E.; Shaheen, Tharwat I.
Abstract: In this study, new stimuli – responsive hybrid hydrogels were achieved via succinylated cellulose nanocrystals (Su-CNC). The innovation was concerned with the inclusion of Su-CNC, at different degree of substitution (DS), into hydrogel network to render it pH and thermo-responsive characters through free radical polymerization reaction with poly(N-isopropylacrylamide) (PNIPAm). The prepared hydrogel was also examined for the in vitro release of Famotidine at different pH values. As clearly evident from the results, all the hydrogels prepared with different DS of Su-CNC, which were nominated as Su-CNC / PNIPAm (1–3), showed a high response to temperature change since their swelling behavior and hydrophilicity were decreased at 35 °C and upwards. This led to the more hydrophobicity character and thus the hydrogel shrinkage occurred. On the other hand, at pH 6, the hydrogels exhibited a significant Equilibrium Swelling Ratio (ESR) attaining 18.1, 17.3 and 16.8 (g/g) for Su-CNC / PNIPAm (1–3), respectively. However, Su-CNC / PNIPAm 2 hydrogel showed a significant response to the pH change from 8 to 2 which was advised to be selected as a potential pH responsive hydrogel for the in vitro Famotidine release. Graphical abstract: Unlabelled Image